Qualitative research with diverse and underserved communities - McClinton, Jeton, 1961-; Hernandez, Arthur E.; Thornton, Alma L. (Current social and cultural issues: challenges and solutions., 2024)
"The purpose of this book is to provide a description and explanation of various qualitative methods and mechanisms of analysis with case study examples. The book will introduce theory, methods, and techniques and can serve a field guide for practice. Though there are many books which describe qualitative research, this book is designed from its inception as a guide to inquiry with individuals from and groups and communities which are underrepresented, marginalized, and/or socially disadvantaged. With this purpose, the book focuses on the meaningfulness of qualitative approaches framed by a commitment to social justice and considers qualitative research with the imperative of involving voiceless, marginalized, unrepresented, or devalued populations."--Provided by publisher.